Pre-analytical variables affecting breast cancer biomarker expression: A controlled single-specimen study of fixation duration, cold ischemia time, and fixative preparation in a low-resource setting - Clément Parfait Ndengue; Paul Jean Adrien Atangana; Gilbert Roger Ateba; Samuel Honoré Mandengue; Emile Telesphore Mboudou; Carole Else Eboumbou Moukoko (PLoS ONE, 2026)
Background Optimal pre-analytical management of breast tissue specimens, particularly formalin fixation, is essential for accurate immunohistochemical (IHC) biomarker assessment in invasive breast cancer. Although international guidelines suggest using 4% neutral buffered formalin with controlled fixation time, many laboratories in low-resource settings deviate from these standards. This study aimed to determine whether three pre-analytical variables — fixation duration, cold ischemia time, and fixative preparation (4% neutral buffered versus 4% non-buffered formaldehyde) — impact the preservation and evaluation of tissue biomarkers in invasive breast cancer. Methods We conducted an exploratory, proof-of-concept, experimental study using fresh mastectomy tissue from a 34-year-old patient with invasive ductal carcinoma (pT4, hormone receptor-positive, HER2-negative, Ki67 = 40%) who had not received neoadjuvant chemotherapy. Fifty microsamples (5–15 mm in length, approximately 1 mm in diameter) were obtained using a 14-gauge core needle biopsy device and divided into four cohorts: (1) 19 samples fixed in 4% neutral buffered formaldehyde for 0.5 to 144 hours; (2) 19 samples fixed in 4% non-buffered formaldehyde for 0.5 to 144 hours; (3) 6 samples with delayed fixation (0.5 to 8 hours) then fixed in neutral buffered formaldehyde for 10 hours; (4) 6 samples with delayed fixation (0.5 to 8 hours) then fixed in non-buffered formaldehyde for 10 hours. Hormone receptors (estrogen receptor-ER, progesterone receptor-PR) and Ki67 expression were evaluated by IHC using the Allred scoring system and current international recommendations. Results Fixative preparation had a statistically significant, yet small, impact on biomarker evaluation. The mean percentage of ER-positive cells was 96.89 ± 0.74% with neutral buffered formaldehyde compared to 94.32 ± 1.51% with non-buffered formaldehyde (p = 0.011). Similar trends were seen for PR (94.89 ± 0.95% vs. 92.63 ± 1.67%, p = 0.027) and staining intensity. However, Allred scores remained unchanged. Fixation duration was significantly correlated with biomarker expression (Spearman ρ between −0.60 and −0.83, p ≤ 0.007), with stable values from 0.5 to 48 h and a significant decline beyond 72 h (one-way ANOVA across fixation windows: all p < 0.01). Cold ischemia time was strongly correlated with decreased biomarker expression regardless of fixative preparation. Hormone receptor expression and Ki67 remained stable with minimal Allred score changes for up to 2 hours of cold ischemia, but significantly decreased after 2 hours, with scores decreasing in proportion to the duration of ischemia (p < 0.05). Conclusions In this single-specimen controlled experiment, non-buffered formaldehyde preserved tissue biomarkers with small but measurable differences relative to neutral buffered formaldehyde for IHC analysis, although these findings require validation in multi-patient studies. Consistent with current guidelines, a cold ischemia time of up to 1 hour maintained adequate biomarker preservation. These preliminary results may be relevant for pathology laboratories in resource-limited settings where neutral buffered formalin may not be easily accessible, and warrant further investigation across diverse tumor types and baseline expression levels, particularly tumors with ER-low-positive (1–10%) or heterogeneous expression.